Validation of the job content questionnaire among hospital nurses in Vietnam - Sasaki, Natsu (2020)
Objectives: The aim of this study was to examine the reliability and validity of the Job Content Questionnaire (JCQ) in Vietnamese among hospital nursing staff. Methods: The 22‐items version of the JCQ was used. This includes four scales: (a) psychological demands (5 items); (b) job control (9 items); (c) supervisor support (4 items); and (d) coworker support (4 items). All 1258 nurses in a general hospital in Vietnam, excluding 11 who were due to retire, were invited to complete the cross‐sectional survey. The internal consistency reliability was estimated using Cronbach's α. Construct validity was examined using exploratory factor analysis (EFA). Convergent validity was evaluated by calculating correlations between the JCQ scores and DASS 21 and overtime work. Results: In total, 949 (75%) of the 1258 eligible nurses completed the survey. Cronbach's α values demonstrated acceptable internal consistency in two scales (supervisor support α = .87; coworker support α = .86), while Cronbach's α was below the acceptable threshold of 0.70 for job control (α = .45) and job demand (α = .50). EFA assuming a four‐factor structure showed a factor structure that was almost identical to the original JCQ, with two items loading on other scales. The subscales of depression, anxiety, and stress response of DASS 21 and the subscales of JCQ were significantly correlated, as expected. Conclusion: The results suggest that the JCQ in Vietnamese can be used with some reliability and validity for examining psychosocial work environment among nurses. Further studies should be done to confirm and expand our findings in a variety of occupational groups and in other Asian low‐ and middle‐income countries.